2013
DOI: 10.1371/journal.pone.0056519
|View full text |Cite
|
Sign up to set email alerts
|

Evening Chronotype Is Associated with Changes in Eating Behavior, More Sleep Apnea, and Increased Stress Hormones in Short Sleeping Obese Individuals

Abstract: BackgroundShort sleep duration and decreased sleep quality are emerging risk factors for obesity and its associated morbidities. Chronotype, an attribute that reflects individual preferences in the timing of sleep and other behaviors, is a continuum from morningness to eveningness. The importance of chronotype in relation to obesity is mostly unknown. Evening types tend to have unhealthy eating habits and suffer from psychological problems more frequently than Morning types, thus we hypothesized that eveningne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
5
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(197 citation statements)
references
References 42 publications
12
165
5
15
Order By: Relevance
“…Recently, Lucassen et al [28] evaluated obese participants (BMI 30-55 kg/m 2 ) ages 18 to 50 years from the Sleep Extension Study by a portable screening device. Eveningtype individuals presented with OSA approximately two times more than morningness individuals independent of BMI and neck circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lucassen et al [28] evaluated obese participants (BMI 30-55 kg/m 2 ) ages 18 to 50 years from the Sleep Extension Study by a portable screening device. Eveningtype individuals presented with OSA approximately two times more than morningness individuals independent of BMI and neck circumference.…”
Section: Discussionmentioning
confidence: 99%
“…In this questionnaire, individuals can be stratified by circadian preference subjectively reported as morning, evening, and neutral type. This circadian preference has been related to several metabolic disturbances 7,8 . Indeed, Yu et al 7 has recently reported that eveningness is significantly linked with metabolic syndrome when compared to morningness.…”
Section: Introductionmentioning
confidence: 98%
“…E. Lucassen с соавт. (2013) продемонстрировали статистически значимое повы-шение ИМТ, стрессовых гормонов (АКТГ в плазме крови в утреннее время, суточной экскреции и адре-налина) и снижение уровней ХС-ЛПВП у больных ожирением с вечерним хронотипом и сном продолжи-тельностью менее 6,5 ч в сутки [15]. У больных ожи-рением с наличием полиморфизма 3111C clock-гена, связанного с вечерним хронотипом (основная группа), отмечались худшие показатели по динамике массы тела через 30 недель немедикаментозной терапии ожи-рения по сравнению с контрольной группой без дан-ных генетических изменений (р=0,039) [16].…”
Section: ожирение и метаболизмunclassified
“…Данные вы-воды согласуются с результатами проведенных ранее исследований, в частности в работе E. Lucassen с соавт. (2013 г) показана достоверная связь вечернего хроно-типа с аномальными формами приема пищи (вечерняя еда, уменьшение количества приемов пищи, увеличе-ние объема порций и их потребление преимущественно во второй половине дня) и высоким уровнем стрессо-вых гормонов у больных ожирением [15]. В отличие от этой работы, по нашим результатам отсутствовала значимая связь хронотипа с СОАС и гормонально-ме-таболическими показателями, а также не выявлено его влияния на степень снижения массы тела.…”
unclassified